PRODUCT SKATEBOARD DALAM FILM “HABIBIE & AINUN” - Andia Rischy (Institut Seni Budaya Indonesia Bandung, 2021)
Currently Film becomes a medium of promotional strategy of a product or called Product Skateboard that is in great demand by advertiser manufacturers. Because watching a movie can attract high attention and involve activities so that the audience is interested in buying the product. Natural placements also make viewers less distracted than ads that appear too much and have a long duration. But not necessarily Product Skateboard is able to run smoothly, but there is also a Product Skateboard where advertiser producers are more concerned about how the product can be seen in the film related to the interests of producers to advertise and the interests of producers to obtain financial support for the filming process. This can create blurring of the boundaries between entertainment and commercial element 2, as well as disrupting the script due to product type mismatches with the scene that existed when the product appeared. Product skateboard marketing that looks at the discrepancy of the year marketed products with a time setting is in one of the films titled